Assessment of the level of maxillary sinus floor in dentulous, edentulous and free end cases on a sample of Malay population using orthopantomogram - Allaw, Belqees A.; Al-Ani, Imad Matloub Dally; Mustafa, Nazih Shaban; Kashmola, Muhanad Ali Hamdon (iMedPub, 2016)
Introduction: Knowledge about the relation between the floor of the maxillary sinus and the teeth\area considered an important and essential for dental practitioners for the planning of many surgical procedures in this area. Objective: The purpose of this study was to assess the level of maxillary sinus floor in dentulous, edentulous and free end cases among Malay population based on gender, and age by using panoramic radiographs. Methods: Sample size was 364 cases including 118 dentulous, 192 edentulous, and 54 free ends. Measuring the distance between maxillary sinus floor and either root apices of upper posterior teeth or residual ridge in dentulous cases, edentulous and free end cases, and study the relation of this distance with gender and age. Results: The distance in dentulous have no relation to the age and gender and vice versa in edentulous and free end cases. Conclusion: The distance not affected by age and gender in dentulous cases, while it is effective in edentulous and free end cases